2023
DOI: 10.1037/prj0000520
|View full text |Cite
|
Sign up to set email alerts
|

Mapping community: A scoping review of clubhouse members’ social networks and their impact on recovery in mental illness.

Abstract: Objective: Social support is an important component of recovery-based interventions for individuals living with severe mental illness (IWSMI). Clubhouses are local community centers that facilitate the development of meaningful relationships among IWSMI through an empowering structure and engagement with the work-ordered day. This review synthesizes research on social networks in Clubhouses to provide insights on the role of supportive relationships in mental illness recovery, including the size and features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Finally, one scoping review suggests that network size is not consistently associated with reported loneliness, social support, recovery, or quality of life. A deep relationship with at least one supportive person may be more or equally valuable than a larger network ( 78 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, one scoping review suggests that network size is not consistently associated with reported loneliness, social support, recovery, or quality of life. A deep relationship with at least one supportive person may be more or equally valuable than a larger network ( 78 ).…”
Section: Resultsmentioning
confidence: 99%
“…Like people with intellectual disabilities, individuals with serious mental illnesses (SMIs) are a uniquely vulnerable population who frequently report lower levels of health literacy than the general population [51,52], and they experience high incidence of chronic illness and early mortality [11]. They are also more likely to have compromised or limited social networks and experience social isolation [53,54]. Thus, this study examined the ways in which social network supports in psychosocial rehabilitation centers (called mental health Clubhouses [55,56] were associated with individual health literacy.…”
Section: Health Literacy and Social Context Findings From The Special...mentioning
confidence: 99%
“…Numerous reviews suggest that the Clubhouse model reduces hospitalizations, promotes employment, and improves the quality of life for Clubhouse members (McKay et al, 2018). Further, reviews have noted the effectiveness of the model in social outcomes (Meyer et al, 2022; Yan et al, 2021). Despite the considerable evidence base, reviews have noted the need for further studies, particularly with a longitudinal design to assess Clubhouse member’s outcomes over time (Battin et al, 2016).…”
Section: Clubhouse Effectivenessmentioning
confidence: 99%